Interactions between Upf1 and the Decapping Factors Edc3 and Pat1 in Saccharomyces cerevisiae - Swisher, Kylie D. (Public Library of Science, 2011)

(untitled)
In Saccharomyces cerevisiae, mRNA transcripts with premature termination codons are targeted for deadenylation independent decapping and 5′ to 3′ decay in a quality control pathway termed nonsense-mediated decay (NMD). Critical factors in NMD include Upf1, Upf2, and Upf3, as well as the decapping enzyme, Dcp2/Dcp1. Loss of Upf2 or Upf3 leads to the accumulation of not only Upf1 and Dcp2 in P-bodies, but also of the decapping-activators Pat1, Dhh1, and Lsm1. An interaction between Upf1 and Dcp2 has been identified, which might recruit Dcp2 to the NMD decapping complex. To determine the nature and significance of the Dcp2-Upf1 interaction, we utilized the yeast two-hybrid assay to assess Upf1 interactions with various mRNA decapping factors. We find that although Dcp2 can interact with Upf1, this interaction is indirect and is largely dependent on the Edc3 protein, which interacts with the N-terminal domain of Upf1 at an overlapping, but not identical, site as Upf2. We also found that Pat1 has an independent two-hybrid interaction with the N-terminus of Upf1. Assessment of both reporter and endogenous NMD transcripts suggest that the decapping stimulators, including Edc3 and Pat1, as well as Edc1 and Edc2, are not essential for NMD under normal conditions. This work defines a larger decapping complex involved in NMD, but indicates that components of that complex are not required for general NMD and might either regulate a subset of NMD transcripts or be essential for proper NMD under different environmental conditions.